Evaluation of the adequacy and usefulness of the audiovisual materials of the College of Mass Communication Library based on user perception - Cardenas, Claire Monique A. (2012)
Audiovisual materials are teaching devices, teaching aids, and educational media or instructional materials. Teachers use them to support their teaching needs and students utilize them, to support their information needs.